Utilization of Antenatal Care, Skilled Birth Assistant and Institutional Delivery in Bangladesh (Dhaka University Journal of Science, 2018)
Maternal mortality is an important phenomenon to assess the overall health status of a society. To reduce maternal mortality the worldwide recognized vital three factors are: antenatal care, presence of skilled birth assistance and selection of place of delivery. This study made an initiative to identify potential risk factors which can influence the three factors employing the Bangladesh Demographic and Health Survey (BDHS), 2014 data. The parameters are estimated using Poisson count model and Logistic regression model. The estimation results indicate that mother’s education level, place of residence, mother’s age at birth, wealth index, husband’s education level, media exposure and region are significant factors for antenatal care visits. The significant factors for skilled birth assistance are mother’s education level, place of residence, wealth index, media exposure and husband’s education level where as place of residence, mother’s education level, wealth index, media exposure and husband’s education level are significant factors for selection of place of delivery. These results may help the policy makers to develop policies that may facilitate the reduction of maternal mortality in Bangladesh.Dhaka Univ. J. Sci. 66(1): 21-27, 2018 (January)